STRATEGI PENGEMBANGAN PENDIDIKAN KONSERVASI PADA MASYARAKAT SUKU TENGGER DI DESA ENCLAVE TAMAN NASIONAL BROMO TENGGER SEMERU - Tri Sayektiningsih; Resti Meilani; E.K.S. Harini Muntasib (Department of Forest Resources Conservation and Ecotourism - IPB University, 2008)
The paper outlines the characteristics and local needs of Tengger Tribe community lived in enclave village of Bromo Tengger Semeru National Park (BTSNP), conservation education conducted for the community, and the needs for developing a strategy of conservation education development for the community to balance their interaction with and the use of BTSNP resources. The research was aimed at determining strategy of conservation education development for the Tengger Tribe community. Data was colected using literature study, interview and observation methods. The research resulted in the main strategy on the development of conservation education for Tengger Tribe community in the enclave village of BTSNP. Considering the strengths, weaknesses, threats, and opportunity occured for developing conservation education for the community, the author suggested that the main strategy should be to implement traditional wisdom based conservation education which focus on skills improvement in local resources management.Keywords: Bromo Tengger Semeru National Park, Tengger Tribe, conservation education, traditional wisdom, skill improvement.